Parametrisation and design of Quadrifilar Helices for use in S-band satellite communications - Fraser, Heather (My University, 2010)
This paper is a discussion on the Multiturn Quadrifilar Helix Antenna (QHA) with particular focus on its application as a ground station antenna for S-band communications with a Low Earth Orbit Satellite. A ground station antenna without a tracking system requires a “saddle” shaped, circularly polarised radiation pattern in order to compensate for the change in distance between it and the antenna on the satellite. The Multiturn Quadrifilar Helix can provide this radiation pattern with correct setting of the parameters of pitch, radius and number of turns. The QHA was simulated according to the adjustment of these parameters and the results were assessed. The most suitable results were found for the antennas with low to mid range of number of turns, radii less than 0.22¸ and pitch less than 0.6¸. A QHA with 3 turns, pitch of 0.6¸ and radius of 0.034¸ was suitable for satellite communications. Simulations showed it to have a gain of 6.16dB at 52± and -2.25dB at 0±. Three separate feed networks: a corporate feed network, 90±-180± Hybrid combination and Wilkinson splitter feed network, for the QHA were designed. The antenna was constructed for each feed network and tested. The constructed antennas all had gains less than predicted by simulation. The QHA using the Corporate Feed network had a gain of approximately 10dB less than expected. The QHA using the 90±-180± Hybrid combination feed network had a gain of approximately 8dB less than expected. The best performing QHA was fed by the Wilkinson splitter feed network. It showed good comparison to the shape of the pattern found in simulation but a gain of approximately 6dB lower than expected